Gold Nanostars For Surface-Enhanced Raman Scattering: Synthesis, Characterization and Optimization - Khoury, Christopher G. (2008)
The controlled synthesis of high-yield gold nanostars of varying sizes, their characterization and use in surface-enhanced Raman scattering (SERS) measurements are reported for the first time. Gold nanostars ranging from 45 to 116-nm in size were synthesized in high-yield, physically modeled and optically characterized using transmission and scanning electron microscopy and UV-Visible absorption spectroscopy. The nanostar characterization involved both studying morphology evolution over time and size as a function of nucleation. The nanostars properties as substrates for SERS were investigated and compared with respect to size. As the overall star size increases, so does the core size, the number of branches and branch aspect ratio; the number of branch tips per star surface area decreases with increasing size. The stars become more inhomogeneous in shape, although their yield is high and overall size remains homogeneous. Variations in star size are also accompanied by shifts of the long plasmon band in the NIR region, which hints towards tuning capabilities that may be exploited in specific SERS applications. The measured SERS enhancement factors suggest an interesting correlation between nanostar size and SERS efficiencies, and were relatively consistent across different star samples, with the enhancement factor estimated as 5×10(3) averaged over the 52-nm nanostars for 633-nm excitation.